WITTGENSTEIN AGAINST THE REALISM/ANTI-REALISM DISTINCTION - George M. Strander (Daimon)
In this Blue Book, Ludwig Wittgenstein puts forward an argument against the general realism/anti-realism distinction in metaphysics. If the argument is right, neither realism nor anti-realism concerning any putative element of reality is permissable. In this paper I am not really concerned with determining whether Wittgenstein´s argument is right, but rather with presenting its structure and the assumptions upon which it rests. The basis of Wittgenstein´s criticism is his assertion that metaphysics is, in general, misguided. This assertion rests on the view that metaphysics involves taking grammatical claims as scientific claims. This view is, in turn, seen to rest on various assumptions located is the text of The Blue Book. The common-sense-realism/idealism distinction is used by Wittgenstein as the particular realism/anti-realism distinction the destruction of which best serves to show the invalidity of the general realism/anti-realism destinction. That common sense makes no hypotheses and is but the grammar of ordinare languaje is a key assumption in this part of Wittgenstein´s argument.